An incident database for improving metro safety: The case of shanghai. (April 2016) - Zhang, Xiaoling; Deng, Yongliang; Li, Qiming; Skitmore, Martin; Zhou, Zhipeng
Highlights: A new metro operation incident database (MOID) is designed for metro incident management. Statistical characteristics of incident is discovered based on the established Shanghai MOID. Three kinds of accident precursors are identified for preventing metro accident in Shanghai. An organizational structure is proposed and discussed to promote the application of MOID. Abstract: Large cities depend heavily on their metro systems to reduce traffic congestion, which is particularly the case with Shanghai, the largest and most developed city in China. For the purposes of enhancing the possibility in quantitative risk assessment and promoting the safety management level in Shanghai metro, an adaptable metro operation incident database (MOID) is therefore presented for containing details of all incidents that have occurred in metro operation. Taking compatibility and simplicity into consideration, Microsoft Access 2010 software is used for the comprehensive and thorough design of the MOID. Based on MOID, statistical characteristics of incident, such as types, causes, time, and severity, are discovered and 24 accident precursors are identified in Shanghai metro. The processes are demonstrated to show how the MOID can be used to identify trends in the incidents that have occurred and to anticipate and prevent future accidents. In order to promote the application of MOID, an organizational structure is proposed from the four aspects of supervision, research, implementation, and manufacturer. This research would be conducive to safety risk analysis in identifying relevant precursors in safety management and assessing safety level as a qualitative tool.